522 Recruitment Optimization: A Strategic Approach to Integrating Recruitment Services through a Coordinated Multidisciplinary Team. (April 2022) - Hudson, Brenda L; Claxton, Gina; Egan, Carmel; Hardwick, Emily; Shwery, Michelle; Bork, Jason; Amin, Waqas; Anderson, Angela; Wiehe, Sarah; Moe, Sharon
Abstract : OBJECTIVES/GOALS: Provide recruitment support via a coordinated application of strategic operations, participant engagement practices, and informatic capabilities best practices. Improve study success through the discovery of optimal recruitment practices, development of needed services, leverage of existing resources, infrastructure and guidance. METHODS/STUDY POPULATION: The optimization effort utilized a variety of methods for engaging participants and obtaining information related to the recruitment needs of study teams. Information was collected from an advisory board and through surveys of a diverse group of investigators and research coordinators examining recruitment barriers as well as current and possible future recruitment services. A workflow of the investigative teams recruitment experience was created to identify strengths, gaps and areas for improvement. This information was used to develop a set of recommendations for the Indiana CTSI leadership. Three pillars were tasked with tackling specific areas through an integrative and collaborative approach: (1) study planning and operations, (2) informatics, and (3) participant engagement and health literacy. RESULTS/ANTICIPATED RESULTS: Key resulting recommendations included: creating a recruitment navigator to direct clients to the most appropriate service(s), adding a community engaged staff member and a digital public engagement specialist to the recruitment services team, redesigning the website navigations, creating participant payment guidelines, creating participant engagement principles guidelines, improving informatics support, and continual evaluation of best practices and innovations in recruitment support. An intake and follow-up survey were created for clients to assess services offered, those used, and ultimately the success of those services in improving recruitment measures. DISCUSSION/SIGNIFICANCE: The optimization efforts have shown a positive response from study teams demonstrated by an uptick of support requests. By taking an intensive strategic planning approach to streamlining recruitment services, the Indiana CTSI has leveraged existing resources to better serve clients in need of critical recruitment assistance.